Evaluasi Kandungan Protein Kasar, Lemak Kasar, Serat Kasar, dan Nilai Fleigh pada Silase Kulit Buah Kakao yang ditambah Molasses dan Tepung Gaplek: Evaluation of Crude Protein, Crude Fat, Crude Fiber, and Fleigh Score Content in Cocoa Pod Husk Silage Supplemented with Molasses and Cassava Flour - Anggi Derma Tungga Dewi; Ririn Angriani; Etha Azizah Hasiib; Syahrio Tantalo (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2025)
Cocoa pod husks still contain several nutrients, making them potentially useful as livestock feed. Nonetheless, cocoa pod husks face limitations such as low crude protein and high crude fiber content. This study aimed to explore the effectiveness of molasses and cassava flour in cocoa pod husk silage on nutrient quality. A Completely Randomized Design (CRD) was applied, with each treatment replicated three times. The treatments consisted of 0% (P0), 10% molasses (P1), 10% cassava flour (P2), and 5% molasses + 5% cassava flour (P3). The observed nutrient qualities were crude protein, crude fiber, and crude fat. The data were analyzed at a 5% level of significance and followed up with the least significant difference test. The results showed that the addition of molasses and cassava flour to cocoa pod husk silage had a statistically significant effect (p < 0.05) on crude fiber content and fiber value, but no significant effect on crude protein or crude fat content. The combination of 5% molasses and 5% cassava flour resulted in the lowest crude fiber content with a good Fleigh value. It can be concluded that the combination of 5% molasses and 5% cassava flour produces the best quality cocoa pod husk silage. Key words:           cassava flour, crude fat, crude fiber, crude protein, cocoa pod husk silage, fleigh score, molasses